Thoughtfully Navigating the Terrain of Teaching English Language Arts: An Examination of Two Teacher Educators’ Literacies Pedagogies - McKee, Lori; Scheffel, Tara-Lynn (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2024)
This paper shares findings from a Self-Study of Teacher Education practice (S-STEP) where we leveraged our long-standing relationship as critical friends to examine our teacher education pedagogies in our elementary English Language Arts courses in 2022-2023. Guided by posthuman perspectives, we consider the relational movements that produced our pedagogies during a currently contentious field mapped by polarizing views in reports, social media, and teacher professional texts. We name movements our literacies pedagogies with/in these challenging times highlighting instances where the context shaped our pedagogies and where our pedagogies moved against the context. This paper offers an invitation to other educators to consider ways that we can create a culture that honours expansive understandings of literacies and creates spaces for curriculum-making and pedagogical inventiveness.